Covert - Chua, Bervyn Lee Ann (Nanyang Technological University, 2023)
Covert is a 3D animated short film developed over the course of 14 months. The story is about a security guard fighting a thief who attempts to steal the museum's prized Jewel. The team consists of Bervyn Chua, Rodolfo Barcelli and Celeste Chia. With our prior experience in creating an award winning short, The Last Stop, we reprised our pipeline of using a game engine to make an animation. Working with a game engine pipeline allowed us to give story and animation centre stage thanks to the advantages it provided, such as: being able to swap out assets, reiterate on lighting and animation without halting the pipeline, all the while shrinking render times to seconds instead of the hours traditional rendering requires.